Namibia : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2008)
The Government of Namibia has a full equity share of four specialist or policy banking corporation. There are a large number of public nonfinancial corporations, in which the government has a part or full ownership share, including public utilities and Air Namibia, the national airline. There are a number of statutorily and nonstatutorily created funds of the central government. There are two important funds for social security and pensions for government employees. Reforming the state-owned enterprise sector is one priority of the government, though the progress has been slow.